Pion, Kaon, and Proton Production in Central Pb-Pb Collisions at √sNN=2.76 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad, N.; Masoodi, A. Ahmad; et al. (AMER PHYSICAL SOC, 2012)
In this Letter we report the first results on pi(+/-), K-+/-, p, and (p) over bar production at midrapidity (vertical bar y vertical bar < 0.5) in central Pb-Pb collisions at root s(NN) = 2.76 TeV, measured by the ALICE experiment at the LHC. The p(T) distributions and yields are compared to previous results at root s(NN) = 200 GeV and expectations from hydrodynamic and thermal models. The spectral shapes indicate a strong increase of the radial flow velocity with root s(NN), which in hydrodynamic models is expected as a consequence of the increasing particle density. While the K/pi ratio is in line with predictions from the thermal model, the p/pi ratio is found to be lower by a factor of about 1.5. This deviation from thermal model expectations is still to be understood.
Keywords: TOTAL CROSS-SECTIONS; QUARK-GLUON PLASMA; HADRON-PRODUCTION; MONTE-CARLO; FREEZE-OUT; QCD; SPECTRUM; Physics